Well-being and mental health interventions for Indigenous people in prison: systematic review. Issue 6 (November 2019) - Perdacher, Elke; Kavanagh, David; Sheffield, Jeanie
Abstract : Background: Indigenous people are overrepresented in prison populations of colonised justice systems, and Indigenous prisoners in these countries are at a particularly high risk of poor mental health and well-being. There is an acute need to ensure the access of these groups to culturally appropriate, evidence-based interventions. Aims: To conduct a systematic review, evaluating quantitative and qualitative evaluations of mental health and well-being interventions designed for Indigenous people in custody. Method: A search of relevant peer-reviewed journal articles to August 2019 was conducted. The focus was on colonised countries under a Western model of justice and health, including Canada, Australia, New Zealand and the USA. The review utilised Scopus, Web of Science, PubMed, PsycNET, EBSCO, Proquest Criminal Justice Database and Informit. Results: Of the 9283 articles initially found, only three quantitative and two qualitative evaluations of mental health or well-being interventions for Indigenous people in custody were identified. None were randomised controlled trials. Culturally based interventions appeared to have high acceptability and potential for increased recovery from trauma, reduced alcohol-related problems and lower reoffending. However, no studies quantitatively assessed mental health or well-being outcomes. Conclusions: As yet there is no high-quality evidence on the impact on mental health and well-being from interventions specifically for Indigenous prisoners, although existing studies suggest programme features that may maximise acceptability and impact. There is a moral, social and practical imperative to build a strong evidence base on this topic.